Analisis Pemenuhan Hak Atas Restitusi Terhadap Anak Sebagai Korban Tindak Pidana Kekerasan Seksual - Ataka Badrudduja; Yeni Widowaty (Indonesian Journal of Criminal Law and Criminology (IJCLC), 2023)
Sexual violence against children can have complex impacts, including physical and non-physical loss and suffering. Children who experience sexual violence need to be protected and recovered psychologically and socially. A form of legal protection for children as victims can be in the form of restitution charged to the perpetrator to fulfill the rights of children as victims. This research aims to find out how the implementation of the right to restitution for children as victims of criminal acts of sexual violence is implemented and how judges consider in making decisions that include requests for restitution for children as victims of criminal acts of sexual violence in the jurisdiction of the Bantul District Court. This research uses a type of juridical-empirical legal research and uses interviews and literature study as data collection techniques. There were 35 cases of criminal acts of sexual violence against children at the Bantul District Court from 2020 to 2022, but only 7 cases included a request for restitution against the victim in the prosecution, and there was 1 case where the judge rejected the request for restitution. In 6 cases where restitution was granted, the victim's right to restitution was not fulfilled because the defendant did not have the good faith to pay restitution.